Public opinions on tax and retail-based tobacco control strategies. Issue Volume 24:Issue e1(2015) (23rd December 2013) - Farley, Shannon M; Coady, Micaela H; Mandel-Ricci, Jenna; Waddell, Elizabeth Needham; Chan, Christina; Kilgore, Elizabeth A; Kansagra, Susan M
Abstract : Background: While tobacco taxes and smoke-free air regulations have significantly decreased tobacco use, tobacco-related illness accounts for hundreds of thousands of annual deaths. Experts are considering additional strategies to further reduce tobacco consumption. Methods: We investigated smokers' (n=2118) and non-smokers' (n=2210) opinions on existing and theoretical strategies, including tax and retailer-based strategies in New York City, across three cross-sectional surveys. Results: Compared with smokers, non-smokers were significantly more likely (p<0.05) to favour all tobacco control strategies. Overall, 25% of smokers surveyed favoured increasing taxes on cigarettes, climbing to 60% if taxes were used to fund healthcare programmes. Among non-smokers, 72% favoured raising taxes, increasing to 83% if taxes were used to fund healthcare programmes. 54% of non-smoking New Yorkers favoured limiting the number of tobacco retail licences, as did 30% of smokers. The most popular retail-based strategies were raising the minimum age to purchase cigarettes from 18 to 21, with 60% of smokers and 69% of non-smokers in favour, and prohibiting retailers near schools from selling tobacco, with 51% of smokers and 69% of non-smokers in favour. Keeping tobacco products out of customers' view, prohibiting tobacco companies from paying retailers to display or advertise tobacco products and prohibiting price promotions were favoured by more than half of non-smokers surveyed, and almost half of smokers. Conclusions: While the support level varied between smokers and non-smokers, price and retail-based tobacco control strategies were consistently supported by the public, providing useful information for jurisdictions examining emerging tobacco control strategies.